A co-occurring disorders intervention for drug treatment court: 12-month pilot study outcomes. Issue 4 (11th November 2020) - Smelson, David; Shaffer, Paige M.; Posada Rodriguez, Camilo; Gaba, Ayorkor; Harter, Jennifer; Pinals, Debra A.; Casey, Sheila C.
Abstract : Purpose: Many individuals in drug treatment courts (DTCs) have co-occurring mental health and substance use disorders (COD), which can negatively impact treatment engagement, behavioral health and criminal justice outcomes. This paper aims to report results of DTC participants with a COD, who received a 12-month wraparound treatment intervention called MISSION-Criminal Justice (MISSION-CJ) alongside DTC to improve treatment engagement and behavioral health outcomes and reduce reincarcerations. Design/methodology/approach: In this pre-post, single-group pilot, 48 clients enrolled and 81% completed 12-month follow-up assessments (N = 39) and weekly MISSION-CJ fidelity for type and intensity of services delivered. Generalized linear mixed models (GLMMs) were computed with a fixed term for fidelity (e.g. high or low MISSION-CJ), time and a fidelity x time interaction term. Findings: Among participants, at 12 months, 81% of the participants remained engaged in treatment at study completion, and 89% had high MISSON-CJ fidelity. Clients demonstrated significant reductions from baseline to 12 months in average nights in jail (B = −0.1849511, p < 0.0344), mental health symptoms via the Behavior and Symptom Identification Scale (BASIS) total and subscale scores (B = −0.121613, p < 0.0186) and trauma symptoms on the PTSD Checklist-5 (PCL-5) (B = −0.928791, p < 0.0138). High MISSION-CJ fidelity further improved criminal justice, and behavioral health outcomes. Originality/value: This was the first reported 12-month MISSION-CJ trial. While feasible to implement, given the design limitations, future research should include a large randomized controlled trial.